Increasing the professionalism of Muhammadiyah high school teachers through assistance in writing and publishing scientific articles - Moh Mirza Nuryady; Tutut Indria Permana; Ndzani Latifatur Rofi’ah; Kurnia Ayu Miranti (Universitas Muhammadiyah Malang, 2023)
Education policy especially for teachers continues to develop. The teacher's policy to be productive in writing scientific articles is one of the important policies that need attention. The purpose of this service is to provide an understanding of scientific articles and improve the ability of teachers to write scientific articles at SMA Muhammadiyah 1 Sumenep. The method used is the classical and individual methods. The classical approach is carried out in the socialization of writing scientific articles related to the writing procedures and benefits of scientific articles. An individual approach is applied when assisting in writing scientific articles from the stages of making backgrounds, methods, discussions, conclusions, abstracts, and writing citations using Mendeley, as well as the process of submitting national proceedings. The results of this mentoring activity found that there were 15 teachers who took part in the socialization activity, but in the writing assistance there were only 9 teachers, and there were 5 scientific articles that were successfully published in national proceedings. The conclusion obtained in this activity is that all teachers at SMA Muhammadiyah 1 Sumenep have understood the benefits and procedures for writing scientific articles, and most teachers are motivated to actively write and publish the results of their scientific writing.